“IDOLS” OF PHILOSOPHICAL KNOWLEDGE - Tagi Bashirov (Research Retrieval and Academic Letters, 2024)
It is knownthateveryprofessionputs a sealonpeople’s health,theirpsychologyandspiritualappearance.Everyoneknowsthatteacherslike to lecture,speakloudlyandtend to repeat what has already been said many times.Mathematicians, due to their habitofprecisionandrigor,tend to resent the vaguenessanduncertainty of humanitariantexts.Theystrivefor the mostpossiblerigorandaccuracy, evenwherethereisnopracticalneed for it.Astronomers,geologistsandglobalistshabituallymeasureevents on largespatial and temporalscales,viewing the worldfrom a bird’s-eye view.Investigatorsandprosecutorstend to suspecteveryoneandsee some kind of maliciousintentineverything,whilelawyers, on the contrary,tendtojustifyevenobviouscrimes.Theseexamples are notdifficult to multiply.Ingeneral, it can be arguedabout the difference in the psychology of peopleengaged in certainfields of activity,about the conditionality of theirmentalmakeup by the kind of thisactivity.Andif the researcherlackscriticality,thoroughnessandlogic,then the specificsandfeatures of cognitiveactivitycharacteristicofhisfieldcaneasilydirecthim to thewrongpath of solvingtheproblems under consideration.Knowingthesefeatureshelps you to be more self-criticalandachievegreaterobjectivity of the knowledge you receive.